Hyperiids (Amphipoda, Hyperiidea) collected during the TALUD cruises in western Mexico. 5. Family Amphithyridae, with the description of a new species of Amphithyropsis Zeidler - Gasca, Rebeca; Suárez-Morales, Eduardo; Hendrickx, Michel E. (Zootaxa, 2021)
In order to complete the information related to the little studied deep-sea planktonic fauna of western Mexico, samples from a wide depth range (surface to 1550 m depth) were obtained using different gear. Six species and 108 individuals of hyperiid amphipods of the family Amphithyridae were collected at 26 localities, including a new species of Amphithyropsis Zeidler, 2016, which is herein described based on an adult male and a gravid female. Other species include Amphithyrus bispinosus Claus, 1879, the most abundant and frequently collected species (70 specimens at 17 localities), A. muratus Volkov, 1982 (11 specimens at 8 localities), A. sculpturatus Claus, 1879 (14 specimens at 7 localities), Paralycaea gracilis Claus, 1879 (10 specimens from 6 localities), and P. hoylei Stebbing, 1888 (one specimen from one locality). Worldwide and regional distributions are provided for each species.